Essential Trace Metals Concentrations in River Watersin Hilla Governorate, Central Iraq - H. HUSSEIN, FALAH; M. AL-TAEE, MAYSON; N. ALKHATEEB, AHMED; M. ABID, FADHIL (Asian Journal of Chemistry, 2010)
The purpose of this work was to provide information on essential trace metals concentrations in Shatt AI-Hilla in Babylon governorate, Iraq. Six sampling stations were chosen along Shatt AI-Hilla, which is a branch of Euphrates river. Water samples were analyzed for temperature, pH and total hardness. The concentrations of the essential trace metals such as chromium, cobalt, copper, iron, manganese, molybdenum, nickel, selenium, vanadium and zinc were evaluated. Water samples from six stations were collected during the period between the 1st of November 2001 and 31st of September 2002. The concentrations of the elements, during the study period, were found to be 40 ± 23, 46 ± 29, 77 ± 43, 60 ± 33, 36 ± 21, 283 ± 217, 50 ± 27, 35 ± 20, 1314 ± 950 and 70 ± 84 μg L-1 respectively. Comparing these results with those recorded for some other rivers as well as the WHO domestic water guidelines, demonstrated that the concentrations of the elements fall within the high values, indicating that waste materials have been thrown into the river which became polluted. However, concentrations of cobalt, iron and manganese were within the WHO limits.